Short Communication: Antagonistic activity of bacteria isolated from coral Acropora sp of Karimunjawa Islands, Indonesia against Acroporid White Syndrome - AGUS SABDONO; AGUS TRIANTO; OCKY KARNA RADJASA; DIAH PERMATA WIJAYANTI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sabdono A, Trianto A, Radjasa OK, Wijayanti DP. 2019. Antagonistic activity of bacteria isolated from coral Acropora sp of Karimunjawa Islands, Indonesia against Acroporid White Syndrome. Biodiversitas 20: 1350-1355. Acroporid White Syndrome (AWS) disease, causing coral death and mortality, has come out as a serious threat to coral reefs in the Karimunjawa Islands, Java Sea. In the present study, the bacterial community associated with the Acroporid were assessed for their antagonistic activity against bacteria associated with AWS disease. A culture collection of 43 bacteria associated with coral Acroporid was established by plating on Zobell’s 2214E. Isolates were screened using the overlay method. The results showed that five isolates (11.62 %) were able to inhibit the growth of the AWS isolates. These isolates were tested further for their consistency of antagonistic activity by using disc-agar diffused method. Based on their consistency, AU5 isolate was selected for study at advance. Polyphasic and phylogenetic analysis were used to characterized AU5 isolate. The DNA sequence analyses demonstrated that this bacterial isolate affiliated with Firmicutes. The AU5 isolate showed high 16S rDNA sequence identity to Virgibacillus salarius strain muzPC213 (99%). The results demonstrated the existence of bacterial coral symbionts with AWS antipathogenic activity on the coral tissue, possibly performing as biocontrol agent to protect the coral Acroporids against AWS outbreaks.